2013
DOI: 10.3727/096368912x656144
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Neural Stem Cell Graft-Induced Structural Repair in Stroke

Abstract: Stem cell therapy ameliorates motor deficits in experimental stroke model. Multimodal molecular imaging enables real-time longitudinal monitoring of infarct location, size, and transplant survival. In the present study, we used magnetic resonance imaging (MRI) and positron emission tomography (PET) to track the infarct evolution, tissue repair, and the fate of grafted cells. We genetically engineered embryonic stem cell-derived neural stem cells (NSCs) with a triple fusion reporter gene to express monomeric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…20 In our study, we choose the Resovist, a clinically approved SPIO particle used in our study, has been demonstrated as a nanoparticle with high uptake and long persistence in human MSC throughout a period of several weeks, 21 our MSCs can be well labeled with 25 mg/mL SPIO particles without affecting the viability and labeling efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…20 In our study, we choose the Resovist, a clinically approved SPIO particle used in our study, has been demonstrated as a nanoparticle with high uptake and long persistence in human MSC throughout a period of several weeks, 21 our MSCs can be well labeled with 25 mg/mL SPIO particles without affecting the viability and labeling efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to transplantation, hNSCs were genetically modified to express a triple fusion (TF) reporter gene encoding monomeric red fluorescent protein (mRFP), firefly luciferase (Luc), and a truncated version of HSV1-tk (HSV-ttk). hNSCs also were labeled with SPIO particles prior to transplantation, thus allowing us to simultaneously track cells by BLI, PET, and MRI and also to measure the functional efficacy of hNSCs on stroke recovery [74]. Using this multimodal imaging strategy, we found that grafted hNSCs reduced the infarct size of moderate strokes in a dose-dependent manner, while larger strokes could not be spared in this manner.…”
Section: Petmentioning
confidence: 99%
“…NSCs can be isolated from the adult striatal tissue [1,2]. They are considered as candidate for cell replacement therapy in various neurological diseases, particularly in ischemic stroke-induced cerebral damages [3][4][5][6][7]. Ischemic stroke accounts for 80 % of all strokes [8].…”
Section: Introductionmentioning
confidence: 99%